Ta'arudh al-Adillah A Multidimensional Maqashid Syari'ah Approach to Building Flexibility in the Application of Islamic Jurisprudence - Abdul Roni, Rusli; Umar, Hasbi; Mukhtar, Mukhtar; Adawiyah, Robi'atul; Muhammad, Pauzi (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This study discusses ta'arudh al-adillah as a multidimensional maqashid syari'ah approach that fosters flexibility and adaptability in the application of Islamic Jurisprudence. The paper has four objectives: to explain the concept of ta'arudh al-adillah within Islamic jurisprudence, to identify the primary causes of ta'arudh al-adillah, to explore methods of resolving ta'arudh al-adillah from the perspective of usul al-fiqh, and to analyze its relevance in contemporary contexts and its implementation based on the maqashid syari'ah approach to build flexibility and adaptability in the application of Islamic law that embodies rahmah (mercy). The study finds that resolving ta'arudh al-adillah is not limited to canceling, selecting, or harmonizing seemingly contradictory evidences but rather determining what is most beneficial (aslah) for current realities. By understanding and applying the principles of ta'arudh al-adillah, Islamic law can adapt to the demands of the modern era without compromising the essence of the syari'ah. This approach encourages innovative ijtihad, providing comprehensive legal solutions grounded in the maqashid al-syari'ah as the spirit of a compassionate and wise shari'ah. [Kajian ini membincangkan tentang ta’arud aladillah yang dinilai sebagai sebuah pendekatan multidimensi maqashid syariah membangun fleksibelitas dan adaptifitas dalam penerapan hukum islam. Ada empat tujuan dan objektif tulisan ini yaitu menjelaskan pengertian ta’arrud adillah dalam hukum Islam, dan mengidentifikasi penyebab utama bagaimana terjadinya ta'arrudh al-adillah serta metode penyelesaian Taarudh al-adillah dalam perspektif ushul fiqh dan relevansinya dalam konteks kontemporer serta implementasinya yang mengacu kepada pendekatan maqashid syariah dalam membangun fleksibelitas dan adaptibelitas penerapan hukum islam yang Rahmah. Kajian ini mendapati bahwa penyelesaian taarudh aladillah tidak hanya tertumpu kepada persoalan membatalkan, meninggalkan atau memilih atau mengharmonikan dalil-dalil yang dilihat kontradik, tetapi mana yang paling aslah terhadap realitas kekinian. Bahkan dengan memahami dan menerapkan prinsip-prinsip ta'arrudh al-adillah, hukum Islam mampu beradaptasi dengan tuntutan zaman tanpa mengabaikan esensi syariah, mendorong ruang ijtihad yang inovatif, dan menyediakan solusi hukum yang komprehensif berlandaskan maqashid al-syari’ah sebagai ruh Syariat yang ramah penuh hikmah.]